A Comparative Study of D-Dimer Levels in Adult Patients with Sickle Cell Anemia at Ahmadu Bello University Teaching Hospital Zaria, Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Introduction:Sickle cell anemia (SCA) is a chronic disease presenting with acute and painful exacerbations with multi-organ affectation. An alteration in the components of hemostasis such as the fibrinolytic system is observed among patients with SCA. Routine care of patients with SCA rarely involves the investigation of this component, and little attention is paid to the role of this system in the evaluation of patients with vaso-occlusive crisis.Objectives:To determine the D-dimer levels and some hematological parameters of adult patients with sickle cell anemia in steady state attending the hematology clinic of Ahmadu Bello University Teaching Hospital (ABUTH) Zaria, Nigeria.Materials and Methods:We conducted a case-control study involving 50 patients with SCA (HbSS) in steady state and 25 healthy volunteers with normal hemoglobin (HbAA) as controls. Steady state refers to absence of acute painful crisis or any changes due to therapy for at least four consecutive weeks after a previous painful crisis. Hemoglobin concentration (Hb), white blood cell count (WBC), and platelet count were determined by hematology analyzer. D-dimer levels were determined by ELISA method using Microplate Reader (Rayto RT-2100C), calibrated to a wavelength of 450 nm. Results were summarized as frequencies, proportions, and median with interquartile range (IQR) where appropriate and the level of significance was set at ≤0.05.Results:The mean age of the patients was 23.80 ± 7.46 years while that of the controls was 24.28 ± 4.8 years (P= 0.76), respectively. The mean hematological parameters of both groups were Hb (8.57 ± 1.33 vs 13. ± 1.29 g/dL,Pvalue